Production Performance and Carcass Traits of Broilers Fed with Sunflower Acid Oil - Jayalakshmi, N.S.; Mathivanan, R.; Amutha, R.; Edwin, S.C.; Viswanathan, K. (International Journal of Poultry Science, 2006)
The influence of sunflower acid oil (SFAO) usage on production performance, carcass traits and economics of broilers were studied. SFAO was analyzed for its ME value by conducting metabolic trial and result revealed that the AME and TME value of SFAO were 4.398 and 4.453 kcal/g, respectively. The feeding trial was conducted by using two hundred commercial, straight run day-old broiler chicks. These chicks were randomly grouped into five treatments with four replicates of ten chicks each and fed basal diet (T1), basal diet with 1 (T2), 2 (T3), 3 (T4) and 4 (T5) percent of SFAO for a period of six weeks. The results revealed that there was no significant difference in body weight gain, cumulative feed consumption, cumulative feed conversion ratio and livability between treatment groups from first week till the end of the experiment. The carcass yield, abdominal fat pad weight and thickness also did not differ significantly between treatments. Inclusion of SFAO at 1, 2 and 3 percent in broiler diet increased the net profit per kg live weight by 2.8, 1.8 and 3.7 percent, respectively as compared to control group. It was concluded that 3 percent SFAO can be safely included in broiler diet without affecting production performance with increase in net profit per kg live weight.